1998
DOI: 10.1089/aid.1998.14.475
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody and Perinatal Transmission of Human Immunodeficiency Virus Type 1

Abstract: The major immunologic determinants for perinatal transmission of human immunodeficiency virus type 1 (HIV-1) remain largely unknown. The presence of maternal neutralizing antibodies has been proposed as an explanation for why the majority of infants born to untreated HIV-1-infected women do not become infected. Using maternal and infant specimens collected as part of a longitudinal cohort study of perinatal transmission in New York City between 1991 and 1995, we successfully obtained primary viral isolates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
2
25
0
2
Order By: Relevance
“…Animal models indicate that antibody can reduce or prevent perinatal transmission of retroviruses (18,20,22,35). The role of maternal neutralizing antibody in prevention of perinatal HIV-1 transmission, however, remains controversial (6,26,28,32,37). Conflicting reports may be due to limits in definitive data, small sample sizes, inconsistent selection of virus source, differences in HIV-1 gene region analyzed, use of widely disparate maternal and infant sample collection time points, and lack of differentiation of the timing of mother-to-child transmission.…”
mentioning
confidence: 99%
“…Animal models indicate that antibody can reduce or prevent perinatal transmission of retroviruses (18,20,22,35). The role of maternal neutralizing antibody in prevention of perinatal HIV-1 transmission, however, remains controversial (6,26,28,32,37). Conflicting reports may be due to limits in definitive data, small sample sizes, inconsistent selection of virus source, differences in HIV-1 gene region analyzed, use of widely disparate maternal and infant sample collection time points, and lack of differentiation of the timing of mother-to-child transmission.…”
mentioning
confidence: 99%
“…However, it seems important that these antibodies should be able to neutralize the HIV-1 strain circulating in the mother's blood during pregnancy/delivery, i.e., to be effective against the autologous viral strain. Autologous neutralizing antibodies have been shown to be important for prevention of vertical mother-to-child HIV-1 transmission (Scarlatti et al 1993a, Hutto et al 1996, Jansson et al 1997, Louisirirotchanakul et al 1999, Lathey et al 1999, although some reports deny the importance of autologous neutralizing antibodies (Husson et al 1995, Hengel et al 1998. In a study carried out by our group no correlation between autologous neutralizing antibodies and VT could be established, although further studies will be necessary to clarify this issue.…”
Section: Humoral Immune Responsementioning
confidence: 62%
“…However, there appears to be no major discussion on the finding that broadly neutralizing antibodies present in high titers will be associated to non-transmission of HIV-1 (Sienna Workshop 1992, Scarlatti et al 1993b, Khouri et al 1995, Hutto et al 1996, Jansson et al 1997, Cologognesi et al 1997, Bongertz et al 1999, Louisirotchanakul et al 1999. Nevertheless, some studies do not detect any protection by neutralizing antibodies in VT (Parekh et al 1991, Kliks et al 1994, Hengel et al 1998, Mabondzo et al 1998. A recent study carried out in monkeys indicated that low titer neutralizing antibodies do not protect at all; only partial protection is achieved, even by antibodies able to neutralize up to 90% of HIV-1 infection at low dilutions; and that, in order to be protective, specific neutralization has to be absolute, neutralizing 100% of the present virus (reviewed by Moore & Burton 1999).…”
Section: Humoral Immune Responsementioning
confidence: 99%
“…Nevertheless, whether maternal NAbs and maternal humoral immunity in general play a role in vertical HIV transmission remains controversial. Several early reports indicated an association between maternal NAbs and protection against vertical transmission (Rossi et al, 1989;Devash et al, 1990;Louisirirotchanakul et al, 1999), but these observations were not confirmed (Bal et al, 1996;Hengel et al, 1998). Since selection for escape HIV-1 variants occurs during transmission, it is possible that non-neutralized variants are transmitted to the infant (Okamoto et al, 1997).…”
Section: Neutralizing Antibodies (Nabs) and Vertical Hiv Transmissionmentioning
confidence: 97%